Exercise Intensity Modulation of Hepatic Lipid Metabolism - Fábio S. Lira; Luiz C. Carnevali; Nelo E. Zanchi; Ronaldo VT. Santos; Jean Marc Lavoie; Marília Seelaender (Journal of Nutrition and Metabolism)
Lipid metabolism in the liver is complex and involves the synthesis and secretion of very low density lipoproteins (VLDL), ketone bodies, and high rates of fatty acid oxidation, synthesis, and esterification. Exercise training induces several changes in lipid metabolism in the liver and affects VLDL secretion and fatty acid oxidation. These alterations are even more conspicuous in disease, as in obesity, and cancer cachexia. Our understanding of the mechanisms leading to metabolic adaptations in the liver as induced by exercise training has advanced considerably in the recent years, but much remains to be addressed. More recently, the adoption of high intensity exercise training has been put forward as a means of modulating hepatic metabolism. The purpose of the present paper is to summarise and discuss the merit of such new knowledge.